Combined neutrophil-lymphocyte ratio and platelet-lymphocyte ratio predicts chemotherapy response and prognosis in patients with advanced gastric cancer - Tetsushi Hirahara; Takaaki Arigami; Shigehiro Yanagita; Daisuke Matsushita; Yasuto Uchikado; Yoshiaki Kita; Shinichiro Mori; Ken Sasaki; Itaru Omoto; Hiroshi Kurahara; Kosei Maemura; Keishi Okubo; et al. (BMC Cancer, 2019)
Abstract Background The neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) are representative blood markers of systemic inflammatory responses. However, the clinical significance of the combination of these markers is unclear. This study aimed to investigate the NLR and PLR in patients with advanced gastric cancer treated with chemotherapy and assess the clinical utility of a new blood score combining the NLR and PLR (NLR-PLR score) as a predictor of tumor response and prognosis. Methods We retrospectively analyzed 175 patients with gastric cancer receiving chemotherapy or chemoradiotherapy. These patients were categorized into progressive disease (PD) and non-PD groups according to tumor response. The NLR and PLR before treatment were examined, and the cut-off values were determined. The NLR-PLR score ranged from 0 to 2 as follows: score of 2, high NLR (> 2.461) and high PLR (> 248.4); score of 1, either high NLR or high PLR; score of 0, neither high NLR nor high PLR. Results With regard to tumor response, 64 and 111 patients had PD and non-PD, respectively. The NLR-PLR score was significantly higher in patients with PD than in those with non-PD (p = 0.0009). The prognosis was significantly poorer in patients with a higher NLR-PLR score than in those with a lower NLR-PLR score (p <  0.0001). Multivariate analysis demonstrated that the NLR-PLR score was an independent prognostic factor for prediction of overall survival (p = 0.0392). Conclusion Low-cost stratification according to the NLR-PLR score might be a promising approach for predicting tumor response and prognosis in patients with advanced gastric cancer.